Sinus Dermoide (International Journal of Medical and Surgical Sciences, 2014)
The dermoid sinus (DS) is a congenital malformation described in humans and canines, due to a development defect of the embryo, in which the skin does not completely separate from the ectodermic neural tube during the embryonic development. The lesion locates along the dorsal midline and manifests as a tubular pouch, which extends from the skin covering advancing through underlying tissues, being able to reach depths from the subcutaneous to the spinal cord. Most important in addressing the DS in humans is the early detection of skin abnormalities; prevention is crucial in infants, as it can prevent future neurological and orthopedic abnormalities. In the Rhodesian Ridgeback breed, breeders assign greater value to dogs that have a hard lock of hair labeled in reverse on the back line, as desirable characteristics in the race, when in fact it is a birth defect.